Endorsement Practices Of Syariah Digital Investment By Influencers: An Islamic Economic Perspective In Ethics And Sustainability Studies - Yulfan Arif Nurohman; Muhammad Sholahuddin; Melia Kusuma; Ircham Suwarsang Putra; Alean Kistiani Hegy Suryana; Nani Irma Susanti; Imronudin Imronudin (UIN Siber Syekh Nurjati Cirebon, 2025)
The rise of influencers who become affiliates of fraudulent investments provides benefits for investors. The younger generation who tend to FOMO will easily suffer losses due to content created by influencers. Where influencers do not necessarily convey information honestly through content created related to digital investment. This study aims to analyze the role of influencers in sharia digital investment. The trend of sharia investment and the use of influencers has increased, making it an opportunity for investors to choose. In fact, in Indonesia, digital investment results in major losses. This study uses a qualitative approach that uses a literature review method as a method used by researchers. The results of the study provide an overview of the importance of influencers maintaining ethics. In the Islamic perspective, it is regulated about the importance of receiving information that is true and providing information that can be accounted for. Islam provides guidance on investments that are far from gharar and destructive. Influencers and investors need to be equipped with good financial literacy and strengthen the principle of caution. Where previously the principle of caution had not been studied in sharia digital investment through influencers